2018
DOI: 10.1016/j.actbio.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Alternating block copolymer-based nanoparticles as tools to modulate the loading of multiple chemotherapeutics and imaging probes

Abstract: Cancer therapy often relies on the combined action of different molecules to overcome drug resistance and enhance patient outcome. Combined strategies relying on molecules with different pharmacokinetics often fail due to the lack of concomitant tumor accumulation and, thus, to the loss of synergistic effect. Due to their ability to enhance treatment efficiency, improve drug pharmacokinetics, and reduce adverse effects, polymer nanoparticles (PNPs) have been widely investigated as co-delivery vehicles for canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…[ 60 ] Additionally, the surface of PU‐Tf NPs also contained lipid molecules that may increase NP affinity for cells. [ 40 ] Future studies that quantify the amount of biologically active Tf on the NP surface would confirm such hypotheses.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…[ 60 ] Additionally, the surface of PU‐Tf NPs also contained lipid molecules that may increase NP affinity for cells. [ 40 ] Future studies that quantify the amount of biologically active Tf on the NP surface would confirm such hypotheses.…”
Section: Discussionmentioning
confidence: 94%
“…The PU NPs used in this study are spherical in shape, as shown by transmission electron cryomicroscopy (Cryo TEM) images (Figure S3, Supporting Information) and previous studies. [ 40 ] Similarly, commercial PS NPs possess a spherical shape. [ 41 ] Commercially available PS NPs and synthesized PU NPs were used and surface‐functionalized with Tf, following published methods, exploiting carbodiimide‐mediated grafting (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations